ПОЧЕМУ ПРАВОПРИМЕНЕНИЕ ПРОТИВ ЧРЕЗМЕРНЫХ ЦЕН В РОССИЙСКОЙ ФЕДЕРАЦИИ НЕДОСТАТОЧНО УСПЕШНО? - Авдашева, Светлана; Корнеева, Дина (Вопросы государственного и муниципального управления, 2017)
In developed competition jurisdictions, excessive pricing is more a subject of academic and expert discussions than an actively used instrument of competition enforcement. Russian competition enforcement is an exception in this regard. During the last ten years the Russian competition authority, the Federal Antirust Service (FAS), made several hundred decisions on the violation of rules prohibiting excessive pricing. The question remains whether Russian enforcement is consistent with international experiences, and which part of enforcement limits a positive welfare effect. To achieve this objective the article explains the targets of excessive price enforcement, the legal standard for excessive pricing, and remedies applied in Russian competition law. The main conclusion is that the selection of targets does not generally contradict the objectives of competition enforcement. There are clear theories of harm specifi c to two of the main target groups: dominant exporting companies that apply third-price discrimination in the domestic market vis-à-vis export markets, and dominant companies that increase prices after deregulation, in case there is no new entry. Standards for proving price excessiveness represent a questionable part of enforcement, and they oft en turn out to be weak under judicial review. The application of either lower or higher standards for establishing price excessiveness results in decreasing the deterrence effect. A fear of decreasing deterrence explains the recent shift from ex-post intervention to ex-ante price remedies.